Cutaneous and pulmonary dirofilariasis due to Dirofilaria repens. (18th June 2015) - Benzaquen, M.; Brajon, D.; Delord, M.; Yin, N.; Bittar, F.; Toga, I.; Berbis, P.; Parola, P.
Summary: Dirofilariasis is a worldwide zoonotic infection that accidentally affects humans. It is caused by filarial nematodes of the genus Dirofilaria, which are transmitted by mosquitoes. Cutaneous dirofilariasis appears as inflammatory lesions that could be consistent with Wells' cellulitis. We present a remarkable case of human infection with Dirofilaria repens, causing both subcutaneous and pulmonary nodules. Abstract : What's already known about this topic? Dirofilariasis is a worldwide zoonotic infection that accidentally affects humans. It is caused by filarial nematodes of the genus Dirofilaria, which are transmitted by mosquitoes. Cutaneous dirofilariasis appears like inflammatory lesions that could be consistent with Wells' cellulitis. What does this study add? We present a remarkable and uncommon case of human infection with Dirofilaria repens, causing both subcutaneous and pulmonary nodules.